Validity of the Digital Module Exploration of Physics Concepts in Making â€œJember Batik Craftsâ€ as an Effort to Support Local Wisdom-Based Multicultural Education - Nuraini, Lailatul; Bektiarso, Singgih; Sani, Safina Aulia; Wulandari, Rike Dwi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The prospective physics teachers was very important to be provided with an understanding regarding the local potential of an area that is integrated into the physics learning process as a strengthening of multicultural education. The use of digital modules in physics learning contains the concept of local Jember wisdom, namely making Jember batik crafts that have never been developed before. This research aimed to examine the validity of digital physics modules containing local wisdom "making batik crafts" to facilitate students’ scientific and digital literacy skills. The research method used is research and development with the ADDIE development model. The study enlisted three expert validators who utilized a validation sheet as their instrument. The method for analyzing the validation data was through descriptive percentage analysis. The results of the validation by the validator showed that the construct aspect showed 90.29% (very good), the content aspect was 85% (very good) and the language aspect was 92.22% (very good). The validation results from the development of this digital module as a whole show that the digital module based on the local wisdom of Jember Batik crafts achieves a validity score of 89.17% which is in the very good category and is very feasible to use. Thus, digital modules based on local wisdom in Jember Batik crafts can then be used in the physics learning process as an alternative to innovative solutions for learning resources based on local wisdom.